Enterprise AJAX : strategies for building high performance web applications - Johnson, Dave, 1980- (Prentice Hall, 2007)
"The core technologies of Ajax are quite straightforward; the hard part is applying them in the real world. Fortunately, the authors have been putting Ajax into practice since long before the term 'Ajax' was even coined. Enterprise AJAX offers excellent coverage of issues rarely explained to date, but frequently encountered by enterprise developers-including architecting of Ajax applications, and how to deal with such concerns as usability, security, and reliability."--DR. MICHAEL MAHEMOFF, PH. D. author of Ajax Design Patterns (AjaxPatterns.org) "Just when you thought you knew all you need to know about Ajax, Dave, Alexei, and Andre force open your cranium and unload a dumptruck full of Enterprise Ajax techniques, best practices, and hard-earned expert insight onto your brain. If you want to mix some serious Ajax into your serious business applications, the solid information and advice you get from this book will let you do so with confidence."--BRENT ASHLEY, Web Developer and Ajax Pioneer "I can't think of any better authors for a book on Enterprise AJAX. The book is sure to be a valuable reference for developers the world over working on the next generation of web applications." -MATT MCKENZIE, Software development manager, LiveCycle, Adobe Systems Inc. "A great resource for writing quality, enterprise-level JavaScript." -CHRISTIAN VAN EEDEN, Senior Application Specialist, Schenker DB Logistics BUILD RELIABLE, SCALABLE, ENTERPRISE-CLASS WEB APPLICATIONS WITH AJAX Writing for enterprise developers, architects, and user interface specialists, the authors explain why AJAX offers such great promise in large-scale development. Next, they systematically introduce today's key AJAX techniques and components. You'll walk through developing frameworks for building AJAX applications that combine data tables, Web forms, charts, search, and filtering: the very systems businesses depend on in CRM, ERP, BI, and beyond. Then, building on this strong foundation, the authors identify proven AJAX architectural patterns, and present case studies drawn from actual .NET and Java AJAX applications. Coverge includes Using AJAX to implement Model-View-Controller (MVC) in the browser Encapsulating user interface functionality to facilitate code reuse and reduce cross-browser development problems Overcoming the unique security challenges associated with AJAX Web applications Optimizing AJAX usability: the "back" button, caching, bookmarking, offline usage, and beyond ...